Probele în procedura fiscală. Jurisprudenţa CJUE//Evidence in tax procedure. The jurisprudence of the Court of Justice of the European Union - Maria Eliza GALAN (Analele Ştiinţifice ale Universităţii "Al.I. Cuza" din Iaşi. Ştiinţe Juridice)
This article aims to highlight the evidence administered in the fiscal procedure by reference to the jurisprudence of the Court of Justice of the European Union. Considering the directions drawn by the CJEU, we propose to analyze the key aspects in the matter of evidence with reference to the stage prior to the trial phase. The purpose of this research is represented by the importance of the perspective of the European court in this matter, taking into account the effect of the CJEU decisions in national law.